2010
DOI: 10.1007/s10339-010-0369-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vision and haptics on categorizing common objects

Abstract: Most research on object recognition and categorization centers on vision. However, these phenomena are likely influenced by the commonly used modality of touch. The present study tested this notion by having participants explore three-dimensional objects using vision and haptics in naming and sorting tasks. Results showed greater difficulty naming (recognizing) and sorting (categorizing) objects haptically. For both conditions, error increased from the concrete attribute of size to the more abstract quality of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Similarly, neither vision nor haptics naturally recovered the taxonomic relationships between the natural seashells used by Gaißert and Wallraven (2012): participants distinguished between concrete categories such as whether the shells used were flat or convoluted, rather than between abstract categories such as gastropods (e.g., sea-snail) vs. bivalves (e.g., oyster). If biological relationships were recovered at all, this was mainly contingent on shape similarities, although vision was better than haptics in this respect (Gaißert and Wallraven, 2012) as it was for the abstract categories studied by Haag (2011).…”
Section: Object Categorizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, neither vision nor haptics naturally recovered the taxonomic relationships between the natural seashells used by Gaißert and Wallraven (2012): participants distinguished between concrete categories such as whether the shells used were flat or convoluted, rather than between abstract categories such as gastropods (e.g., sea-snail) vs. bivalves (e.g., oyster). If biological relationships were recovered at all, this was mainly contingent on shape similarities, although vision was better than haptics in this respect (Gaißert and Wallraven, 2012) as it was for the abstract categories studied by Haag (2011).…”
Section: Object Categorizationmentioning
confidence: 99%
“…For example, Haag (2011) used realistically textured models of familiar animals that retained real-life size relations, and required visual and haptic categorization on the basis of size (big/small in real life), domesticity (wild/domestic), and predation (carnivore/herbivore). Errors increased as the basis of categorization moved from concrete (size) to abstract (predation) and were consistently greater in haptics than vision (Haag, 2011).…”
Section: Object Categorizationmentioning
confidence: 99%
See 1 more Smart Citation
“…While much is known about visual shape processing ( Haushofer et al, 2008 ; Peelen et al, 2014 ), less information is available regarding tactile shape processing ( Klatzky et al, 1985 ; Hernández-Pérez et al, 2017 ; Metzger et al, 2019 ). A series of studies comparing visual and tactile perceptual spaces with familiar objects have revealed that the human perception of familiar objects is not solely determined by the physical features of objects but is influenced by high-level cognitive abilities, including memory ( Amedi et al, 2002 ; Norman et al, 2008 ; Haag, 2011 ; Metzger and Drewing, 2019 ) and prior knowledge of objects for integrating sensory systems ( Ernst and Bülthoff, 2004 ). While other studies have used parametric shape models, such as shell-shaped 3D objects ( Gaißert et al, 2008 , 2010a , 2011 ; Gaißert and Wallraven, 2012 ), it is difficult to capture the shape complexity of natural objects with parametric approaches and avoid possible confounds or special cases in object shapes ( Haushofer et al, 2008 ; Lee Masson et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lederman & Klatzky [26] analyzed how humans categorize common, everyday objects, while Haag [27] compared visual and haptic categorization of toy objects, which resembled miniaturized animals. While these studies have shown that humans are impressively good at haptic recognition and classification of familiar objects, such stimulus sets have a number of limitations.…”
Section: Introductionmentioning
confidence: 99%